2016
DOI: 10.3390/geosciences6020022
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Use of Absolute Dating Techniques in Ancient Construction Materials

Abstract: The reconstruction of the chronology of historical buildings is a tricky issue, as usually there are not historical documents that allow the assessment of construction phases, and some materials are hardly reliable for the use of dating techniques (e.g., stone). However, in the last two decades, important advances on the use of absolute dating methods on building materials have increased the possibilities of reconstructing building chronologies, although some advances are still scarcely known among archaeologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…It is also a typical Group B sample with low C content, high DISCREP and large proportion of microbial SOM in the extract. However, its age is considerably older (AGE EX 2620 cal BP, AGE RES 5810 cal BP) than the other samples from agricultural settings and, as in the case of the Montealegre mortar, it is probably not representative of the age of the construction of the pavement but of original constituents of the fabric used for manufacturing (Sanjurjo-Sánchez 2016).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It is also a typical Group B sample with low C content, high DISCREP and large proportion of microbial SOM in the extract. However, its age is considerably older (AGE EX 2620 cal BP, AGE RES 5810 cal BP) than the other samples from agricultural settings and, as in the case of the Montealegre mortar, it is probably not representative of the age of the construction of the pavement but of original constituents of the fabric used for manufacturing (Sanjurjo-Sánchez 2016).…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, the post-construction physico-chemical environment is different from that of soils. Neither SOM EX nor SOM RES could provide a reliable date for the construction of the wall; rather they would represent either the age of the organic material used for the mortar (Sanjurjo-Sánchez 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that the reuse of bricks originating from older structures was a frequent practice (for instance: Galli et al 2004;Bailiff et al 2010;Guibert et al 2012Guibert et al , 2019. That is the reason why we have been focusing on lime mortar dating for some years, as we consider that it is directly related to the construction (Zacharias et al 2002;Goedicke 2003Goedicke , 2011Martini and Sibilia 2006;Feathers et al 2008;Gueli et al 2010;Sanjurjo-Sanchez 2016;Panzeri et al 2019;Sanjurjo-Sanchez et al forthcoming). The basic premise of mortar dating by OSL is that quartz in the sand used for making lime mortar is optically zeroed during the preparation process (optical bleaching).…”
Section: Introductionmentioning
confidence: 99%
“…The question of time (and dating of events) has a preeminent role in Lyell's work and in [2] human artefacts are considered as potential elements for dating geologic formations (and their absence in older formations is considered an indication of the recent origin of humans). The papers of Sanjurjo-Sánchez [14] and of Straulino-Mainou and collaborators [15] continue this tradition, in these cases using geologic materials or materials derived from geologic sources as tools for dating built structures.…”
mentioning
confidence: 98%
“…Other papers in this Special Issue [14][15][16][17] reflect the architectural and cultural value of other geologic materials (including materials derived from geologic materials).…”
mentioning
confidence: 99%